Can HLA-G predict disease course in rheumatoid arthritis patients?. (December 2013) - Rizzo, Roberta; Bortolotti, Daria; Baricordi, Olavio R; Farina, Ilaria; Padovan, Melissa; Govoni, Marcello
Rheumatoid arthritis remains a major clinical problem, with many patients having persistent systemic inflammatory disease, resulting in progressive erosive joint damage and high levels of disability. The goal of rheumatoid arthritis therapy has shifted to initiate treatment early and aggressively to achieve remission, or low disease activity as quickly as possible. To achieve this 'treat-to-target' concept, it is necessary to identify new biomarkers for disease progression and treatment follow-up, and to identify new therapeutic targets. The focus of this review is to summarize current research regarding the expression of HLA-G molecules in rheumatoid arthritis and the possible implications for the future management of the disease.